Development and Evaluation of Digital Assembly Instructions: Cognitive Support in Final Assembly - Andersson, Anton; Trogen, Wilhelm (My University, 2020)
Customer demands have greatly changed in recent times within the automotive sector. Customers are now demanding highly customizable products. This forces the final assembly to be highly manual in order to be flexible enough to handle the variations in production. The manual assembly combined with highly varied operations leads to increased complexity for operators. This has created the need for a cognitive support for operators in final assembly. This thesis has developed and evaluated digital assembly instructions for cognitive support of operators in final assembly of the automotive sector. The instructions are focused on highlighting variations and important tasks. The digital assembly instructions were evaluated based on information quality through consulting a set of experts within information handling in production systems. It was concluded that it is possible to create digital assembly instructions with high information quality as a real-time support for operators in the final assembly. These instructions are able to support operators in their assembly work and reduce complexity. The increased cognitive support reduces the mental load on operators and thus improves cognitive ergonomics. This support is also likely leading to a reduction of the total number of quality errors in production. However, the instructions are likely to have a limited impact on physical ergonomics. This thesis has thus provided industry with a tool that can be used to improve production in terms of quality, cognitive support and work environment sustainability.
Keywords: Digitalization, Instructions, Information Quality, Operator Support; Final Assembly, Quality, Ergonomics, Mass Customization